Dynamics and diversity: ethnic employment differences in England and Wales, 1991 - 2001 - Kenneth Clark; Stephen Drinkwater (Institute for the Study of Labor (IZA), 2005)
This paper uses microdata from the 1991 and 2001 Population Censuses to examine differences in the employment experiences of ethnic minorities living in England and Wales. It focuses on two main issues, firstly the extent to which the employment position of the main ethnic minority groups changed between the two Census dates and secondly, a detailed examination of employment amongst ethnic groups in 2001. In relative terms, it is found that there was an improvement in the employment rates of most ethnic minority groups over the period, some of which could be explained by enhanced levels of observable characteristics. However, the employment gap between Whites and certain ethnic minority groups remains extremely large. Religion, local deprivation and educational qualifications are important influences on employment for many of these groups.
Keywords: J15; J21; J7; 330; employment; ethnic minorities; discrimination